2011
DOI: 10.1080/15287394.2011.600665
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Effects of eNOS Gene Polymorphisms (T-786C and Glu298Asp) on Nitric Oxide Levels in a Methylmercury-Exposed Population

Abstract: Nitric oxide (NO) is a potent vasodilator with multiple protective effects involved in the regulation of cardiovascular functions. Endothelial NO synthase (eNOS) gene polymorphisms and environmental factors, such as mercury (Hg) exposure, may influence NO levels and increase the risk of cardiovascular damage. The aim of this study was to determine the role of the T-786C and Glu298Asp polymorphisms of the eNOS gene on nitrite concentrations following Hg exposure in humans. It was postulated that Hg exposure mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Two studies examined the contribution of MeHg to cardiovascular disease and found that polymorphisms in eNOS were not associated with increased risk of cardiovascular disease; however, a polymorphism in intron 4 increased susceptibility to cardiovascular disease after MeHg exposure by modulating NO levels [30, 32]. In addition, plasma eicosapentaenioic+docosahexaenoic acid or erythrocyte-mercury were not found to be associated with the risk of MI [30, 32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies examined the contribution of MeHg to cardiovascular disease and found that polymorphisms in eNOS were not associated with increased risk of cardiovascular disease; however, a polymorphism in intron 4 increased susceptibility to cardiovascular disease after MeHg exposure by modulating NO levels [30, 32]. In addition, plasma eicosapentaenioic+docosahexaenoic acid or erythrocyte-mercury were not found to be associated with the risk of MI [30, 32].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, plasma eicosapentaenioic+docosahexaenoic acid or erythrocyte-mercury were not found to be associated with the risk of MI [30, 32]. Future studies should aim to address the contribution of genetics and low-level mercury exposure to disease, taking into consideration the age of exposure and the age of testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several GSH-related enzymes are highly polymorphic, and epidemiological studies demonstrated that these polymorphisms may affect the metabolism of Hg (Goyer and Clarkson 2001;Gundacker et al 2010). Moreover, other studies were carried out concerning the relationship between other polymorphisms and adverse health effects induced by Hg exposure (de Marco et al 2011;Echeverria et al 2010;Heyer et al 2009). The GST genes, especially GSTM1 (mu) and T1 (theta), are important since they present a deletion that results in impaired catalytic activity associated with greater sensitivity to toxic compounds.…”
Section: Gst Polymorphisms and Methylmercury Metabolism 961mentioning
confidence: 99%
“…Polymorphisms did not seem to influence the decreased nitric oxide (NO) production as it was found to be predominantly due to Hg, age and gender. Their findings suggest that there is not an association between increased risk for cardiovascular disease in MeHg-exposed subjects and eNOS gene polymorphisms (T-786C and Glu298Asp) 84 . The same group investigated the contribution of the 27-nt tandem repeat of intron 4 of the eNOS gene to NO production, which could enhance susceptibility to cardiovascular disease in the MeHg-exposed study population.…”
Section: Modifiers Of Toxicitymentioning
confidence: 96%